INTERDISCIPLINARY INTEGRATION IN THE COURSE OF STUDYING WEB TECHNOLOGIES AND COMPUTER GRAPHICS - Andrey V. Kolesnikov; Svetlana N. Sirenko (Открытое образование (Москва), 2016)
The expediency of interdisciplinary integration in large-scale introduction of the competence approach is substantiated. The methodology for interdisciplinary integration is presented in the article. The authors demonstrate this methodology on the example of two disciplines: «The development and maintenance of information web-resources» and «Computer Graphics and Multimedia.»